Measuring the Radiopacity of Luting Cements, Dowels, and Core Build-up Materials with a Digital Radiography System Using a CCD Sensor - Brian J. Rasimick, BS;1 Steven Gu, PhD;2 Allan S. Deutsch, DMD;3 (Journal of Prosthodontics, 2007)
This study assessed the radiopacity of five luting cements, five dowels, and five core buildup materials using two target distances